Analisis Kepemimpinan Transformasional Membangun Inovatif Capabillity dalam Meningkatkan Kinerja Sumber Daya Manusia - Teti Safari (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2022)
This study aims to develop a leadership theory that builds innovative capabillity for organizations in the modern era. Innovative Capabillity is the mechanism that underlies the effect of transformational leadership on creativity. Innovative Capabillity aims to improve the performance of lecturer human resources who work in the education industry such as lecturers. This study involved 100 lecturer human resources. Data was collected using a questionnaire and analyzed using Smart PLS analysis. The results showed that there is a significant positive influence between Transformaional leadership on lecturer human resource performance and individual performance. In addition, Innovative Capabillity is also proven to moderate the relationship between transformational leadership and lecturer human resource performance. The implication is that transformational leadership will be proven to increase the performance of lecturers' human resources, if organizational leaders are able to build lecturers' innovation capabilities.